Challenges and Opportunities for Digital Education Financing Against the Digital Infrastructure Gap - Basuki, Rahmat Rizki; Ahmad, Masduki; Rochimah, Heni (Universitas Pahlawan Tuanku Tambusai, 2025)
Digital transformation in the world of education requires comprehensive and equitable integration of technology, especially at the primary education level. Studies from Wahyudi and Jatun (2024) and Nazira, Zahra, and Gusmaneli (2024) show that the use of digital technology such as computers, the internet, and interactive learning platforms has opened up opportunities to increase flexibility, collaboration, and personalization in the teaching and learning process. Learning models such as flipped classroom, blended learning, and hybrid learning have been proven to increase student motivation and participation. However, behind these opportunities, there are still big challenges in the form of a glaring digital infrastructure gap between regions and between educational institutions. Inequality of internet access, limited technological devices, low digital literacy, and lack of training for teachers are serious obstacles to the implementation of digital learning equally. In addition, complex geographical and socioeconomic conditions further widen the digital divide between urban and rural areas. In this context, digital education financing is an important instrument to bridge infrastructure disparities and increase human resource capacity. Targeted financing strategies should include the procurement of tools, strengthening teacher training, developing curriculum-based local content, and supporting policies that promote equitable access to technology. Thus, digital education financing can be positioned as a strategic investment in creating an inclusive, adaptive, and equitable education system in the digital era.